Thrombolysis for Cerebral Ischemia - Fugate, Jennifer E.; Giraldo, Elias A.; Rabinstein, Alejandro A. (Frontiers in Neurology, 2010)
The care for patients with acute ischemic stroke has been revolutionized by the clinical application of fibrinolysis. Intravenous recombinant tissue plasminogen activator (rt-PA) has been proven to improve functional outcomes following acute ischemic stroke and can be administered to a select group of patients up to 4.5 hours after symptom onset. Time from symptom onset to thrombolysis is the most important determinant of the success of treatment, with greatest efficacy if given within 90 minutes. Hospitals should implement standardized processes and protocols for acute stroke to guide immediate patient assessment, brain imaging, drug administration, and post thrombolysis care. In this article we review the clinical application of thrombolysis, care of acute stroke patients, current evidence regarding fibrinolysis, and future direction of penumbral imaging to select candidates for reperfusion therapies.